Immunogenic change after percutaneous microwave ablation in pulmonary malignancies: Variation in immune cell subsets and cytokines in peripheral blood - Zhang, Liang; Zhang, Mingming; Wang, Jun; Li, Yang; Wang, Taijie; Xia, Jianguo; Feng, Bo; Shen, Jialin (Frontiers in Immunology, 2022)
Introduction To investigate immunogenic changes after percutaneous microwave ablation (MWA) in pulmonary malignancies. Methods Twenty-two consecutive patients with pulmonary malignancies who underwent percutaneous lung tumor MWA were prospectively enrolled in this study. Peripheral blood samples were collected on the day before (D0) and one month (M1) after MWA. Changes in immune cell subsets (CD3+, CD4+, and CD8+ T cells, and B, natural killer, regulatory T (Treg), and CD3-CD20+ cells) and cytokines (interleukin [IL]-2, 4, 6, 10, 17A, tumor necrosis factor [TNF]-α, and interferon-γ) were noted and compared. Progression-free survival (PFS) and potentially related factors were analyzed. Results The proportion of CD8+ T cells increased from 22.95 ± 7.38% (D0) to 25.95 ± 9.16% (M1) (p = 0.031). The proportion of Treg cells decreased from 10.82 ± 4.52% (D0) to 8.77 ± 2.05% (M1) (p = 0.049). The IL-2 concentration was also decreased from 1.58 ± 0.46 pg/mL (D0) to 1.26 ± 0.60 pg/mL (M1) (p = 0.028). The reduction in Treg cells predicted PFS independently of clinical prognostic features in multivariate analysis (hazard ratio = 4.97, 95% confidence interval: 1.32–18.66, p = 0.018). A reduction in the proportion of Treg cells was observed in 15 patients (68.2%) and the average of the reduction was 2.05 ± 4.60%. Those patients with a reduction in the proportion of Treg cells that was more than average showed a significantly longer median PFS time than those with a reduction that was less than average (16 months vs. 8.5 months, p = 0.025). Discussion Percutaneous MWA of pulmonary malignancies leads to immunogenic changes. The reduction in the proportion of Treg cells was independently associated with PFS.